Marta’s story: a female principal leading in challenge contexts - Cruz González, Cristina; Pérez, Marta; Domingo Segovia, Jesús (Taylor & Francis, 2020)
Recent international research highlights the importance of a strong professional identity based on pedagogical leadership to achieve educational improvement. Several studies indicate a clear relationship between the role of gender identity and the development of a leadership identity. This article tells the story of a female school principal in a Spanish school context. Using a biographical narrative approach, we explore how this female principal built a professional identity oriented towards leadership based on professional commitment and social justice. This study is part of a more extensive international research project whose main objective is to explore the factors that influence the construction of a professional leadership identity for school principals. The analysis was based on an outpouring of deep reflections through a professional biogram. We identified a series of key events in Marta’s life that had a clear professional and personal impact and consolidated her current professional identity. Marta’s story shows the influence of gender, personal life factors, socio-economic status, and the socio-political environment on the development of a professional identity of leadership along with the challenges encountered as a woman. Facing these challenges has led to the re-construction of an identity that is more oriented towards social equality and professional commitment.
Keywords: Liderazgo; leadership; female principal; management; school improvement